Visualizing the interplay of fear and desire in English learner's imagined identities and communities. (November 2021) - Ahn, So-Yeon
Abstract: The present study aims to understand how English learners make sense of themselves in relation to English and how they view the impact of English on their future lives. Grounded on the notion of imagined identity and communities (Pavlenko & Norton, 2007 ), the study explores how 46 Korean undergraduates marshal various non-arbitrary signs to depict their past/current and imagined English-speaker identities and communities mediated by desires and failures in their drawings and written narratives. Coupled with a narrative analysis, a multimodal analysis was employed to better understand the ways the graphic representations and written narratives orchestrate a complex set of identity attributes as multiple modes establish representative, symbolic values. The findings highlight the combination of visual and verbal means of data collection in gaining a deeper understanding of learner perspectives toward English learning as well as the imagined identities envisioned in the current globalised world. The study argues that a multimodal framework provides a milieu for learners to vocalize and reflect on their experiences, beliefs, and attitudes. Concentrating on primary emotions including desire and fear, the study captures how such emotional facets play a role in the shaping of identity and further influence learners' pursuit of language learning.